1994
DOI: 10.1123/ijsn.4.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Acute Changes in Vitamin B6, Status in Endurance Athletes before and after a Marathon

Abstract: The vitamin status of 13 endurance athletes was determined by whole blood (microbiological) and urine 4-pyridoxic acid (4-PA) (HPLC), serum vitamin (pyridoxal, pyridoxol, pyridoxamin) (HPLC), and erythrocyte α- EGOT measurements with the aid of 7-day records. In addition, blood and serum samples and urine were collected before (Time A), directly after (Time B), and 2 hr after a marathon race (Time C). The total energy intake was 12,303 ± 3,464 Wday (34% fat, 48% carbohydrates, 14% protein). The vitamin int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Differences in physical activities and experimental models may explain those discrepancies. On the other hand, increased concentrations of PLP have been described after exercise in marathon runners and attributed to the mobilization of the hepatic and erythrocytic reservoirs (24); therefore, an association of independent effects of acute exercise on changes in plasma B vitamins and aminothiols cannot be excluded in our study.…”
Section: Discussionmentioning
confidence: 85%
“…Differences in physical activities and experimental models may explain those discrepancies. On the other hand, increased concentrations of PLP have been described after exercise in marathon runners and attributed to the mobilization of the hepatic and erythrocytic reservoirs (24); therefore, an association of independent effects of acute exercise on changes in plasma B vitamins and aminothiols cannot be excluded in our study.…”
Section: Discussionmentioning
confidence: 85%
“…In spite of reported intakes that meet dietary recommendations, several studies have documented poor vitamin B 6 status (Telford et al 1992;Fogelholm et al 1993;Manore 1994Manore , 2000Rokitzki et al 1994b). For example, Telford et al (1992) studied 86 male and female athletes before and after an 8-month training period.…”
Section: Dietary Intake and Status Of Vitamin B 6 In Active Adultsmentioning
confidence: 92%
“…Although no studies directly investigated the effects of riboflavin on performance in athletes, it was reported that dieting and exercise increase the intake of riboflavin needed to maintain adequate status 17. Several researchers have shown that exercise modifies pyridoxine metabolism with one study reporting losses of 1 mg during a marathon race 18. However, there are no studies on the effects of pyridoxine supplementation on performance per se.…”
Section: Vitamin Bmentioning
confidence: 99%